Aldosterone induces left ventricular subclinical systolic dysfunction: a strain imaging study. Issue 2 (February 2018) - Chen, Zheng-Wei; Huang, Kuan-Chih; Lee, Jen-Kuang; Lin, Lung-Chun; Chen, Ching-Way; Chang, Yi-Yao; Liao, Che-Wei; Wu, Vin-Cent; Hung, Chi-Shen; Lin, Yen-Hung
Abstract : Background: Primary aldosteronism is associated with a higher incidence of left ventricular (LV) hypertrophy and diastolic dysfunction than essential hypertension. However, systolic function via endocardial measurements is similar between patients with primary aldosteronism and essential hypertension. Speckle-tracking echocardiography is a sensitive tool which can detect subclinical impairments in systolic function. The aim of this study was to investigate aldosterone-induced subclinical impairments in systolic function. Methods: We prospectively enrolled patients with primary aldosteronism and essential hypertension and analyzed their clinical data, biochemical data, and echocardiographic parameters, including myocardial strain [global longitudinal strain (GLS)]. Results: Thirty-six patients with primary aldosteronism and 31 patients with essential hypertension were enrolled for analysis. The patients with primary aldosteronism had significantly lower serum potassium levels, lower plasma renin activity, higher aldosterone-to-renin ratio (ARR), and higher 24-h urinary aldosterone levels than patients with essential hypertension. With regards to echocardiographic parameters, the patients with primary aldosteronism had a thicker ventricular wall and higher LV mass index than those with essential hypertension. Most importantly, we found significant degradation of GLS in the patients with primary aldosteronism compared with those with essential hypertension (−17.84 ± 2.36 vs. −20.13 ± 2.32, P  < 0.001). In correlation analysis, GLS was significantly correlated with serum potassium level, LV mass index, log-transformed plasma renin activity, log-transformed ARR, and log-transformed 24-h urinary aldosterone levels (all P  < 0.05). Multivariate linear regression analysis further identified log-transformed ARR (β = 0.771, 95% confidence interval: 0.011–1.530, P  = 0.047), and log-transformed 24-h urinary aldosterone level (β = 1.765, 95% confidence interval: 0.01–3.529, P  = 0.050) as independent factors correlated with GLS. Conclusion: Patients with primary aldosteronism have a lower magnitude of GLS than patients with essential hypertension, suggesting that aldosterone induces a subclinical decline in LV systolic function.